Philosophy of education - Duka, Cecilio D (Manila, 2006)
This book is simple contribution to help Filipino learners especially in the various teacher training institutions to have an easy-to-read and much more easy to understand reference material in a subject which is considered by many as incomprehensible
Keywords: Education -- Philiosophy